Antyczne kamieniołomy Proconnesos. Zarys problematyki - Grala, Katarzyna (Folia Praehistorica Posnaniensia, 2018)
Authors of this article visited the Marmara island in August 2000 during a short research stay. It was aimed at recognition of at the current condition of the quarries and their ancient remains, preparation of photo and graphic documentation as well as collection of samples for petrographic, chemical. X-rays, and isotopie analyses. The quarries have been functioning since the ancient times until the present day. A marble called the “Marmara-White” is extracted from them. During construction of two new breakwaters in Saraylar, next to which the quarries are located, a Roman and early Byzantine cemetery was found that led to the archaeological studies of the island and consequently to the renewed interest in marble distribution in ancient times.